Perlindungan Hukum Bagi Konsumen Atas Produk Yang Melanggar Etika Periklanan - Anak Agung Ngurah Gede Wiratdika; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2021)
Regarding the development of communication and information, there are several types of print media and electronic media, therefore business actors must be more creative and innovative when promoting their products, and good advertisements must be related to truth, honesty, or correct information. Receiving accurate and honest information is an important consumer right for businesses to provide. This study explains the procedure for consumers to file a lawsuit for losses as well as obligations and sanctions against business actors for products whose promotion violates advertising ethics. This thesis uses a normative legal search with a legal and conceptual approach. The results of this discussion explain about consumers who file lawsuits for losses with the procedures established by BPSK, the responsibility of business actors based on product liability as regulated in Article 19 paragraph (2) of the UUPK and the sanctions there are three, namely civil sanctions, criminal sanctions, and administrative sanctions.